2022
DOI: 10.1111/head.14370
|View full text |Cite
|
Sign up to set email alerts
|

Impact of unilateral trigeminal neuralgia on bilateral ocular surface alterations

Abstract: Objective: To evaluate ocular surface alterations in both eyes of patients with unilateral trigeminal neuralgia (TN) compared with controls.Background: Corneal nerves mainly originate from the trigeminal nerve, and neurosensory abnormalities are important factors in ocular surface alterations and dry eye etiopathogenesis.Methods: Twenty-four patients with idiopathic unilateral TN and 24 healthy controls with similar sex and age distributions were included in this cross-sectional study conducted from February 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
0
0
Order By: Relevance
“…The trigeminal nerve is also important for reflex tear release, the blink reflex, and the release of neurotrophic factors that are important for ocular surface health [ 23 , 24 ]. In their study, Altaş et al found that even if trigeminal neuralgia is unilateral, ocular surface alteration and dry eye are seen in both eyes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…The trigeminal nerve is also important for reflex tear release, the blink reflex, and the release of neurotrophic factors that are important for ocular surface health [ 23 , 24 ]. In their study, Altaş et al found that even if trigeminal neuralgia is unilateral, ocular surface alteration and dry eye are seen in both eyes [ 25 ].…”
Section: Discussionmentioning
confidence: 99%